Role of transcriptional regulation in auxin-mediated response to abiotic stresses - Marzi, Davide; Brunetti, Patrizia; Saini, Shashank Sagar; Yadav, Gitanjali; Puglia, Giuseppe Diego; Dello Ioio, Raffaele (Frontiers in Genetics, 2024)
Global climate change (GCC) is posing a serious threat to organisms, particularly plants, which are sessile. Drought, salinity, and the accumulation of heavy metals alter soil composition and have detrimental effects on crops and wild plants. The hormone auxin plays a pivotal role in the response to stress conditions through the fine regulation of plant growth. Hence, rapid, tight, and coordinated regulation of its concentration is achieved by auxin modulation at multiple levels.Beyond the structural enzymes involved in auxin biosynthesis, transport, and signal transduction, transcription factors (TFs) can finely and rapidly drive auxin content in specific tissues. Auxin Response Factors (ARFs) such as the ARF4,7, 8,19 and many other TF families, such as WRKY and MADS, have been identified to play a role in modulating various auxin-mediated responses in recent times. Here, we review the most relevant and recent literature on TFs associated with the regulation of the biosynthetic, transport, and signalling auxin pathways and miRNA-related feedback loops in response to major abiotic stresses. Knowledge of the specific role of TFs may be of utmost importance in counteracting the effects of GCC on future agriculture and may pave the way for increased plant resilience.